2006
DOI: 10.1002/9780470988640
|View full text |Cite
|
Sign up to set email alerts
|

Control of Primary Metabolism in Plants

Abstract: Evaluation of the transcriptome and genome to inform the study of metabolic control in plants OLIVER THIMM, OLIVER E. BLÄSING, BJORN USADEL and YVES GIBON 2.3.3 Mitochondrial and chloroplast proteomes 2.3.4 Other subcellular proteomes 2.3.5 A stamp of authenticity for the subcellular protein postcode? 2.4 Quantitative analyses of the proteome 2.4.1 Examples of quantitative proteomics 2.4.2 The use of high-throughput measurements of enzyme activity as a proxy for quantitative proteomics 2.5 The use of proteomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 817 publications
0
1
0
Order By: Relevance
“…Recently, we have also shown that UV radiation alone, and in combination with elevated atmospheric CO 2 concentration, alters N allocation between leaves and roots of European beech saplings, leading to changes in leaf and root C:N stoichiometry and morphological traits (Uchytilová et al, 2019). C:N stoichiometry can be considered as one of the most relevant indicators of source:sink balance and can regulate expression of several genes involved in N metabolism (Nunes-Nesi et al, 2010), secondary metabolism (Royer et al, 2013), photosynthesis (Ruiz-Vera et al, 2017; Foyer et al, 2018), and plant biomass allocation (Kruse et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have also shown that UV radiation alone, and in combination with elevated atmospheric CO 2 concentration, alters N allocation between leaves and roots of European beech saplings, leading to changes in leaf and root C:N stoichiometry and morphological traits (Uchytilová et al, 2019). C:N stoichiometry can be considered as one of the most relevant indicators of source:sink balance and can regulate expression of several genes involved in N metabolism (Nunes-Nesi et al, 2010), secondary metabolism (Royer et al, 2013), photosynthesis (Ruiz-Vera et al, 2017; Foyer et al, 2018), and plant biomass allocation (Kruse et al, 2010).…”
Section: Discussionmentioning
confidence: 99%